Preparation method of composite solid electrolyte membrane and composite solid electrolyte membrane

Through the hot pressing process of polyethylene oxide, lithium carboxymethyl cellulose and lithium salt, composite solid electrolyte membrane was prepared, which solved the problems of environmental protection and high ionic conductivity in the preparation of solid polymer electrolytes, and achieved high efficiency. Environmentally friendly electrolyte membrane preparation.

CN119133588AActive Publication Date: 2024-12-13DONGFENG MOTOR GRP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411121030.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2024-12-13
Estimated Expiration
2044-08-15

AI Technical Summary

Technical Problem

The existing preparation methods of solid polymer electrolytes cannot take into account high ionic conductivity and environmental protection. The solution casting process has problems such as toxic solvent pollution, low film formation efficiency, recrystallization and unevenness.

Method used

A mixture of polyethylene oxide, lithium carboxymethylcellulose and lithium salt was used for infiltration and vacuum drying, followed by hot pressing, and a composite solid electrolyte membrane was prepared by controlling the proportion of plasticizers and process parameters.

Benefits of technology

Without using organic solvents, the ionic conductivity and environmental protection of the composite solid electrolyte membrane are improved, the pollution and low efficiency of solution casting are avoided, and the mechanical properties of the membrane are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133588A_ABST
    Figure CN119133588A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of solid electrolyte membranes, in particular to a preparation method of a composite solid electrolyte membrane and the composite solid electrolyte membrane. The preparation method comprises the following steps: mixing polyethylene oxide, lithium carboxymethyl cellulose and lithium salt to obtain a mixture; infiltrating the mixture by using a plasticizer so as to promote the mixture to generate a plasticizing reaction, thereby obtaining an infiltrated mixture; carrying out vacuum drying on the infiltrated mixture to remove redundant plasticizer to obtain a solid electrolyte membrane raw material; carrying out hot pressing on the solid electrolyte membrane raw material to obtain a composite solid electrolyte membrane; wherein the weight m1 of the plasticizer and the weight m2 of the mixture meet the relational expression: m1: m2 = (0.9-1.1): 1; according to the preparation method, the ionic conductivity of the composite solid electrolyte membrane can be improved to 1.50 * 10 <-4 > S / cm or above, and meanwhile, the environmental protection property of the composite solid electrolyte membrane is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solid electrolyte membrane preparation, and in particular to a preparation method of a composite solid electrolyte membrane and a composite solid electrolyte membrane. Background Art

[0002] If there is extrusion, impact, short circuit and other conditions during the operation of traditional lithium-ion batteries with carbonate alkyl electrolytes, it will cause electrolyte volatilization and leakage problems, which may easily cause thermal runaway of lithium-ion batteries and lead to safety accidents. However, if lithium-ion batteries with solid electrolytes are used, there will be no electrolyte volatilization and leakage problems. Therefore, lithium-ion batteries with solid electrolytes have significantly improved safety compared to lithium-ion batteries with carbonate alkyl electrolytes. However, the solid electrolyte used in traditional lithium-ion batteries is a solid inorganic electrolyte, which has poor mechanical properties. Therefore, the solid electrolyte of lithium-ion batteries at this stage mostly uses a solid polymer electrolyte.

[0003] However, solid polymer electrolytes are usually prepared by solution casting. Although the solution casting method is efficient, there are still many problems: (1) The solution casting process will produce a large amount of toxic solvent vapor and pollute the environment; (2) The film forming efficiency of the solution casting method is low; (3) The solution casting process requires a long time of vacuum drying, which may cause the polymer to recrystallize during the vacuum drying process, affecting the ionic conductivity of the solid polymer electrolyte; (4) The solution casting process may also cause polymer deposition and lead to uneven electrolyte membranes, affecting the ionic conductivity of the solid polymer electrolyte. Therefore, the existing preparation methods of solid polymer electrolytes cannot take into account both the high ionic conductivity of solid polymer electrolytes and the environmental friendliness of the process. Summary of the invention

[0004] The present application provides a method for preparing a composite solid electrolyte membrane and a composite solid electrolyte membrane to solve the following technical problem: how to balance the environmental friendliness and high ionic conductivity of a solid polymer electrolyte preparation process.

[0005] In a first aspect, the present application provides a method for preparing a composite solid electrolyte membrane, the preparation method comprising:

[0006] mixing polyethylene oxide, lithium carboxymethyl cellulose, and a lithium salt to obtain a mixture;

[0007] Using a plasticizer to impregnate the mixture to promote a plasticization reaction of the mixture to obtain an impregnated mixture;

[0008] vacuum drying the impregnated mixture to remove excess plasticizer to obtain a solid electrolyte membrane raw material;

[0009] Hot pressing the solid electrolyte membrane raw material to obtain a composite solid electrolyte membrane;

[0010] The weight m1 of the plasticizer and the weight m2 of the mixture satisfy the relationship: m1:m2=(0.9-1.1):1.

[0011] Optionally, the infiltration temperature is 75° C. to 85° C., and the infiltration time is ≥12 h.

[0012] Optionally, the vacuum drying temperature is 75° C. to 85° C., and the vacuum drying time is 30 min to 120 min.

[0013] Optionally, the content of residual plasticizer in the solid electrolyte membrane raw material and the mass ratio of the solid electrolyte membrane raw material satisfy: the residual plasticizer: the solid electrolyte membrane raw material ≤ 0.1.

[0014] Optionally, the temperature of the hot pressing is 50° C. to 80° C., and the time of the hot pressing is 0.5 min to 1.5 min.

[0015] Optionally, the hot pressing pressure is 5 MPa to 20 MPa.

[0016] Optionally, the lithium salt includes at least one of the following:

[0017] Lithium bis(trifluoromethanesulfonyl imide), lithium perchlorate, lithium bis(fluorosulfonyl imide), lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium bis(oxalatoborate).

[0018] Optionally, the plasticizer includes at least one of the following:

[0019] Ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate.

[0020] Optionally, the weight m3 of the polyethylene oxide, the weight m4 of the lithium carboxymethyl cellulose and the weight m5 of the lithium salt satisfy the relationship: m3:m4:m5=(4-7):(4-1):2.

[0021] In a second aspect, the present application provides a composite solid electrolyte membrane, which is prepared by the preparation method described in the first aspect.

[0022] Optionally, the composite solid electrolyte membrane has a thickness of 20 μm to 200 μm.

[0023] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0024] The present application provides a method for preparing a composite solid electrolyte membrane, the preparation method comprising: mixing polyethylene oxide, lithium carboxymethyl cellulose and lithium salt to obtain a mixture; impregnating the mixture with a plasticizer to induce a plasticization reaction in the mixture to obtain an impregnated mixture; vacuum drying the impregnated mixture to remove excess plasticizer to obtain a solid electrolyte membrane raw material; hot pressing the solid electrolyte membrane raw material to obtain a composite solid electrolyte membrane; wherein the weight m1 of the plasticizer and the weight m2 of the mixture satisfy the relationship: m1:m2=0.9~1.1:1; the preparation method uses polyethylene oxide and lithium carboxymethyl cellulose as raw materials, the lithium carboxymethyl cellulose has a large number of hydroxyl groups and lithium ions, and the lithium carboxymethyl cellulose with a large number of hydroxyl groups has good compatibility with polyethylene oxide during the hot pressing stage, and the lithium ions can open the cellulose The internal molecular channel can improve the lithium ion flux, so that the ionic conductivity of the composite solid electrolyte membrane can be improved without adding an organic solvent. At the same time, the lithium carboxymethyl cellulose has good tensile strength and tensile strain. After hot pressing, the lithium carboxymethyl cellulose can inhibit the formation of lithium dendrites of the composite solid electrolyte membrane. In addition, the mass ratio of the plasticizer to the mixture can be 0.9-1.1:1, so that there is a sufficient amount of plasticizer in the mixture. The sufficient amount of plasticizer can increase the mixing uniformity of polyethylene oxide, lithium carboxymethyl cellulose and lithium salt to improve the ionic conductivity of the composite solid electrolyte membrane. In addition, the sufficient amount of plasticizer can improve the plasticity of the mixture, which is convenient for the subsequent composite solid electrolyte membrane to be only hot pressed, thereby avoiding the use of a large amount of organic solvents. Therefore, through the preparation method, the ionic conductivity of the composite solid electrolyte membrane can be improved while improving the environmental protection of the composite solid electrolyte membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0026] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0027] Figure 1 A schematic flow chart of a method for preparing a composite solid electrolyte membrane is provided for an embodiment of the present application;

[0028] Figure 2 A product schematic diagram of a composite solid electrolyte membrane is provided for an embodiment of the present application;

[0029] Figure 3 Schematic diagram of the comparison of the AC impedance of the composite solid electrolyte membrane obtained in Example 1 of the present application and Comparative Example 1. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0031] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within the range; for example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range; in addition, whenever a numerical range is indicated in this document, it is meant to include any cited numbers (fractions or integers) within the indicated range.

[0032] In this document, the terms including "including" and "including" mean "including but not limited to". Relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. "And / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone; where A and B can be singular or plural. "At least one" means one or more, and "plurality" means two or more; "at least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items; for example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple. Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0033] It should be noted that among the many polymers used in solid polymer electrolytes, polyethylene oxide has become one of the most promising polymers for solid polymer electrolytes due to its good lithium salt solubility and ion complexing ability. However, the crystallinity of polyethylene oxide is relatively high at room temperature, which leads to the low ion conductivity of polyethylene oxide at room temperature (about 10 -8 S / cm). Carboxymethyl cellulose can be added to polyethylene oxide to improve its performance. Since carboxymethyl cellulose contains a large number of hydroxyl groups, carboxymethyl cellulose with a large number of hydroxyl groups has good compatibility with polyethylene oxide. In addition, the carboxyl groups of carboxymethyl cellulose can be easily replaced by metal ions. Therefore, the solid electrolyte formed by polyethylene oxide and carboxymethyl cellulose has good eco-friendliness, low cost and additional ion transport characteristics.

[0034] Figure 1 The present invention provides a schematic diagram of a method for preparing a composite solid electrolyte membrane;

[0035] like Figure 1 As shown, the present application embodiment provides a method for preparing a composite solid electrolyte membrane, the preparation method comprising:

[0036] S1. Mixing polyethylene oxide, lithium carboxymethyl cellulose and a lithium salt to obtain a mixture;

[0037] S2. impregnating the mixture with a plasticizer to induce a plasticizing reaction of the mixture to obtain an impregnated mixture;

[0038] S3. The impregnated mixture is vacuum dried to remove excess plasticizer to obtain a solid electrolyte membrane raw material;

[0039] S4. hot pressing the solid electrolyte membrane raw material to obtain a composite solid electrolyte membrane;

[0040] Wherein, the weight m1 of the plasticizer and the weight m2 of the mixture satisfy the relationship: m1:m2=(0.9-1.1):1;

[0041] In these embodiments, the weight m1 of the plasticizer and the weight m2 of the mixture can satisfy the relationship: m1:m2=(0.9-1.1):1, so as to ensure that there is a sufficient amount of plasticizer in the mixture. On the one hand, a sufficient amount of plasticizer can increase the mixing uniformity of polyethylene oxide, lithium carboxymethyl cellulose and lithium salt to improve the ionic conductivity of the composite solid electrolyte membrane. On the other hand, a sufficient amount of plasticizer can improve the plasticity of the mixture, making it convenient to subsequently composite the solid electrolyte membrane only by hot pressing, thereby avoiding the use of a large amount of organic solvents.

[0042] The weight m1 of the plasticizer and the weight m2 of the mixture may satisfy the relationship: m1:m2=0.9:1, 1.0:1 or 1.1:1.

[0043] It should be noted that lithium carboxymethyl cellulose is an effective electrode binder that can enhance intercrystalline adhesion and improve lithium ion flux. The coulombic efficiency and charge and discharge capacity of lithium carboxymethyl cellulose are higher than those of sodium carboxymethyl cellulose. In addition, the inherent tensile strength and tensile strain of lithium carboxymethyl cellulose are beneficial to inhibiting the formation of lithium dendrites in the composite solid electrolyte membrane.

[0044] It should be noted that the preparation process of lithium carboxymethyl cellulose is:

[0045] Under an inert gas atmosphere, sodium carboxymethyl cellulose and a mixed solution of ethanol and acetic acid (the volume ratio of ethanol as a numerator and acetic acid as a denominator is 85:15) are reacted at 35° C. for 3 hours to obtain a mixture; the mixture is then filtered, washed with a mixed solution of ethanol and water (the volume ratio of ethanol as a numerator and acetic acid as a denominator is 85:15), and then dried in a vacuum oven at 80° C. to obtain carboxymethyl cellulose acid;

[0046] In an inert gas atmosphere, carboxymethyl cellulose acid was reacted with a mixture of lithium hydroxide monohydrate, ethanol and water at 50°C for 3 hours. After the reaction was completed, acetic acid was used to neutralize the mixture to pH 7 to eliminate the residual hydroxide (OH - ) to obtain a reaction product; the reaction product was filtered multiple times using a mixture of ethanol and water (the volume ratio of ethanol as the numerator and acetic acid as the denominator was 85:15), and then dried in a vacuum oven at 80° C. to obtain pure lithium carboxymethyl cellulose.

[0047] In some optional embodiments, the soaking temperature is 75°C to 85°C, and the soaking time is ≥12h;

[0048] In these embodiments, the impregnation temperature can be 75°C to 85°C, and the impregnation time is generally ≥12h, which can promote sufficient mixing between the plasticizer and the mixture to improve the plasticity of the mixture and improve the uniformity of mixing of polyethylene oxide, lithium carboxymethyl cellulose and lithium salt in the mixture, thereby facilitating the subsequent composite solid electrolyte membrane only by hot pressing to avoid the use of a large amount of organic solvents.

[0049] The temperature of the soaking may be 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C or 85°C.

[0050] In some optional embodiments, the vacuum drying temperature is 75°C to 85°C, and the vacuum drying time is 30min to 120min;

[0051] In this embodiment, the vacuum drying temperature can be 75°C to 85°C, and the vacuum drying time can be 230min to 120min. The excess plasticizer in the infiltration mixture can be removed by vacuum drying to prevent the plasticizer from affecting the electrochemical and mechanical properties of the composite solid electrolyte membrane, thereby improving the ionic conductivity of the composite solid electrolyte membrane and the mechanical properties of the composite solid electrolyte membrane.

[0052] The vacuum drying temperature may be 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C or 85°C.

[0053] The vacuum drying time can be 30 min, 60 min, 90 min or 120 min.

[0054] In some optional embodiments, the mass ratio of the content of the plasticizer in the solid electrolyte membrane raw material to the solid electrolyte membrane raw material is ≤0.1;

[0055] In this embodiment, the content of plasticizer in the solid electrolyte membrane raw material and the mass ratio of the solid electrolyte membrane raw material are generally ≤0.1, indicating that the content of plasticizer in the solid electrolyte membrane raw material is within an appropriate range, which can avoid the influence of excess plasticizer on the electrochemical properties and mechanical properties of the composite solid electrolyte membrane, thereby improving the ionic conductivity of the composite solid electrolyte membrane and the mechanical properties of the composite solid electrolyte membrane.

[0056] In some optional embodiments, the temperature of the hot pressing is 50°C to 80°C, and the time of the hot pressing is 0.5min to 1.5min;

[0057] In this embodiment, the hot pressing temperature can be 50°C to 80°C, and the hot pressing time can be 0.5min to 1.5min, which can promote the conversion of the solid electrolyte membrane raw material into a composite solid electrolyte membrane so that the composite solid electrolyte membrane has sufficient thickness and sufficient mechanical properties, thereby improving the ionic conductivity of the composite solid electrolyte membrane and the mechanical properties of the composite solid electrolyte membrane.

[0058] The temperature of the hot pressing may be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C.

[0059] The heat pressing time can be 0.5 min, 1.0 min or 1.5 min.

[0060] In some optional embodiments, the hot pressing pressure is 5 MPa to 20 MPa;

[0061] In this embodiment, the hot pressing pressure may be 5 MPa to 20 MPa, which may promote the conversion of the solid electrolyte membrane raw material into a composite solid electrolyte membrane so that the composite solid electrolyte membrane has sufficient thickness and sufficient mechanical properties.

[0062] The pressure of the hot pressing can be 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa, 10 MPa, 11 MPa, 12 MPa, 13 MPa, 14 MPa, 15 MPa, 16 MPa, 17 MPa, 18 MPa, 19 MPa or 20 MPa.

[0063] In some optional embodiments, the lithium salt includes at least one of the following:

[0064] Lithium bis(trifluoromethanesulfonyl imide), lithium perchlorate, lithium bis(fluorosulfonyl imide), lithium hexafluorophosphate, lithium tetrafluoroborate and lithium bis(oxalatoborate);

[0065] In this embodiment, the lithium salt may include at least one of lithium bis(trifluoromethanesulfonyl imide), lithium perchlorate, lithium bis(fluorosulfonyl imide), lithium hexafluorophosphate, lithium tetrafluoroborate and lithium dioxalatoborate, which can reduce the risk of lithium dendrites in the composite solid electrolyte membrane, thereby improving the ionic conductivity of the composite solid electrolyte membrane.

[0066] In some optional embodiments, the plasticizer includes at least one of the following:

[0067] Ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate;

[0068] In this embodiment, the plasticizer may include at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate. The plasticizer can be used to increase the mixing uniformity of polyethylene oxide, lithium carboxymethyl cellulose and lithium salt to improve the ionic conductivity of the composite solid electrolyte membrane. In addition, the plasticizer can also increase the plasticity of the mixture, making it convenient to subsequently composite the solid electrolyte membrane only by hot pressing, thereby avoiding the use of a large amount of organic solvents.

[0069] In some optional embodiments, the weight m3 of the polyethylene oxide, the weight m4 of the lithium carboxymethyl cellulose and the weight m5 of the lithium salt satisfy the relationship: m3:m4:m5=(4-7):(4-1):2;

[0070] In this embodiment, the weight m3 of polyethylene oxide, the weight m4 of lithium carboxymethyl cellulose and the weight m5 of lithium salt can satisfy the relationship: m3:m4:m5=(4-7):(4-1):2, which can promote sufficient mixing between polyethylene oxide, lithium carboxymethyl cellulose and lithium salt to facilitate the subsequent conversion of these raw materials into a composite solid electrolyte membrane by hot pressing.

[0071] The weight m3 of the polyethylene oxide, the weight m4 of the lithium carboxymethyl cellulose and the weight m5 of the lithium salt can satisfy the relationship: m3:m4:m5=4:4:2, 4:4:2, 4:3:2, 4:2:2, 4:1:2, 5:4:2, 5:4:2, 5:3:2, 5:2:2, 5:1:2, 6:4:2, 6:4:2, 6:3:2, 6:2:2, 6:1:2, 7:4:2, 7:4:2, 7:3:2, 7:2:2 or 7:1:2.

[0072] Figure 2 A schematic diagram of a composite solid electrolyte membrane provided by an embodiment of the present application is shown by way of example;

[0073] Based on a general inventive concept, such as Figure 2 As shown, an embodiment of the present application provides a composite solid electrolyte membrane, and the composite solid electrolyte membrane is prepared by the preparation method.

[0074] The composite solid electrolyte membrane is realized based on the above-mentioned preparation method. The specific steps of the preparation method can refer to the above-mentioned embodiment. Since the composite solid electrolyte membrane adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.

[0075] In some optional embodiments, the thickness of the composite solid electrolyte membrane is 20 μm to 200 μm;

[0076] In these embodiments, the thickness of the composite solid electrolyte membrane may be 20 μm to 200 μm, which means that the thickness of the composite solid electrolyte membrane is thin enough to improve the ionic conductivity of the composite solid electrolyte membrane while maintaining sufficient mechanical properties.

[0077] The thickness of the composite solid electrolyte membrane can be 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm, 190μm or 200μm.

[0078] The present application is further described below in conjunction with specific examples. The experimental methods in the following examples that do not specify specific conditions are usually measured according to industry standards; if there are no corresponding industry standards, they are carried out according to common international standards, conventional conditions, or conditions recommended by the manufacturer.

[0079] Example 1

[0080] like Figure 2 As shown, a method for preparing a composite solid electrolyte membrane comprises:

[0081] S1. 0.7 g of polyethylene oxide, 0.1 g of lithium carboxymethyl cellulose and 0.2 g of lithium salt were mixed and placed in a glass bottle, and then moved into a glove box to obtain a mixture of polyethylene oxide and lithium carboxymethyl cellulose;

[0082] S2. Weigh 1.0 g of plasticizer, add the plasticizer to the mixture of polyethylene oxide, lithium carboxymethyl cellulose and lithium salt, stir and mix, and then infiltrate the stirred mixture to induce a plasticizing reaction of the mixture to obtain an infiltrated mixture;

[0083] S3. The impregnated mixture is vacuum dried to remove excess plasticizer, and the residual amount of plasticizer is verified by a thermogravimetric analyzer to obtain a solid electrolyte membrane raw material;

[0084] S4. hot pressing the solid electrolyte membrane raw material to obtain a composite solid electrolyte membrane, denoted as CMC-Li1-PEO-LiTFSI;

[0085] The weight of the plasticizer m1 and the weight of the mixture m2 satisfy the relationship: m1:m2=1:1.

[0086] The immersion temperature was 80°C and the immersion time was 12 h.

[0087] The vacuum drying temperature was 80°C and the vacuum drying time was 60 min.

[0088] The mass ratio of the plasticizer content in the solid electrolyte membrane raw material to the solid electrolyte membrane raw material is ≤0.1.

[0089] The hot pressing temperature was 60°C and the hot pressing time was 1.0 min.

[0090] The hot pressing pressure was 10 MPa.

[0091] The lithium salt is lithium bis(trifluoromethanesulfonyl)imide.

[0092] The plasticizer is propylene carbonate.

[0093] The weight m3 of polyethylene oxide, the weight m4 of lithium carboxymethyl cellulose and the weight m5 of lithium salt satisfy the relationship: m3:m4:m5=7:1:2.

[0094] Example 2

[0095] Based on the contents disclosed in Example 1, the following modifications are further made:

[0096] The weight of polyethylene oxide was 0.6 g, the weight of lithium carboxymethyl cellulose was 0.2 g, the weight of lithium salt was 0.2 g, and the weight of plasticizer was 1.0 g.

[0097] The weight m3 of polyethylene oxide, the weight m4 of lithium carboxymethyl cellulose and the weight m5 of lithium salt satisfy the relationship: m3:m4:m5=6:2:2.

[0098] The obtained composite solid electrolyte membrane is recorded as CMC-Li2-PEO-LiTFSI.

[0099] Example 3

[0100] Based on the contents disclosed in Example 1, the following modifications are further made:

[0101] The weight of polyethylene oxide was 0.5 g, the weight of lithium carboxymethyl cellulose was 0.3 g, the weight of lithium salt was 0.2 g, and the weight of plasticizer was 1.0 g.

[0102] The weight m3 of polyethylene oxide, the weight m4 of lithium carboxymethyl cellulose and the weight m5 of lithium salt satisfy the relationship: m3:m4:m5=5:3:2.

[0103] The obtained composite solid electrolyte membrane is recorded as CMC-Li3-PEO-LiTFSI.

[0104] Example 4

[0105] Based on the contents disclosed in Example 1, the following modifications are further made:

[0106] The weight of polyethylene oxide was 0.4 g, the weight of lithium carboxymethyl cellulose was 0.4 g, the weight of lithium salt was 0.2 g, and the weight of plasticizer was 1.0 g.

[0107] The weight m3 of polyethylene oxide, the weight m4 of lithium carboxymethyl cellulose and the weight m5 of lithium salt satisfy the relationship: m3:m4:m5=4:4:2.

[0108] The obtained composite solid electrolyte membrane is recorded as CMC-Li4-PEO-LiTFSI.

[0109] Example 5

[0110] Based on the contents disclosed in Example 1, the following modifications are further made:

[0111] The soaking temperature was 75°C.

[0112] The vacuum drying temperature was 75°C and the vacuum drying time was 120 min.

[0113] The hot pressing temperature was 80°C and the hot pressing time was 0.5 min.

[0114] The hot pressing pressure was 5 MPa.

[0115] The obtained composite solid electrolyte membrane is recorded as CMC-Li5-PEO-LiTFSI.

[0116] Example 6

[0117] Based on the contents disclosed in Example 1, the following modifications are further made:

[0118] The soaking temperature was 85°C.

[0119] The vacuum drying temperature was 85°C and the vacuum drying time was 60 min.

[0120] The hot pressing temperature was 50°C and the hot pressing time was 1.5 min.

[0121] The hot pressing pressure was 20 MPa.

[0122] The obtained composite solid electrolyte membrane is recorded as CMC-Li6-PEO-LiTFSI.

[0123] Comparative Example 1

[0124] Based on the contents disclosed in Example 1, the following modifications are further made:

[0125] No lithium carboxymethyl cellulose was added, the weight of polyethylene oxide was 0.8 g, the weight of lithium salt was 0.2 g, and the weight of plasticizer was 1.0 g.

[0126] The obtained composite solid electrolyte membrane is recorded as PEO-LiTFSI.

[0127] Comparative Example 2

[0128] Based on the contents disclosed in Example 1, the following modifications are further made:

[0129] The weight of polyethylene oxide was 0.7 g, the weight of lithium carboxymethyl cellulose was 0.5 g, the weight of lithium salt was 0.2 g, and the weight of plasticizer was 1.0 g.

[0130] The obtained composite solid electrolyte membrane is recorded as Li1-PEO-LiTFSI.

[0131] Comparative Example 3

[0132] Based on the contents disclosed in Example 1, the following modifications are further made:

[0133] The immersion temperature was 70°C.

[0134] The obtained composite solid electrolyte membrane is denoted as Li2-PEO-LiTFSI

[0135] Comparative Example 4

[0136] Based on the contents disclosed in Example 1, the following modifications are further made:

[0137] The immersion temperature was 90°C.

[0138] The obtained composite solid electrolyte membrane is denoted as Li3-PEO-LiTFSI

[0139] Comparative Example 5

[0140] Based on the contents disclosed in Example 1, the following modifications are further made:

[0141] The vacuum drying temperature was 70°C and the vacuum drying time was 120 min.

[0142] The obtained composite solid electrolyte membrane is recorded as Li4-PEO-LiTFSI.

[0143] Comparative Example 6

[0144] Based on the contents disclosed in Example 1, the following modifications are further made:

[0145] The vacuum drying temperature was 90°C and the vacuum drying time was 60 min.

[0146] The obtained composite solid electrolyte membrane is recorded as Li5-PEO-LiTFSI.

[0147] Comparative Example 7

[0148] Based on the contents disclosed in Example 1, the following modifications are further made:

[0149] The hot pressing temperature was 40°C and the hot pressing time was 2.0 min.

[0150] The hot pressing pressure was 25 MPa.

[0151] The obtained composite solid electrolyte membrane is recorded as Li6-PEO-LiTFSI.

[0152] Comparative Example 8

[0153] Based on the contents disclosed in Example 1, the following modifications are further made:

[0154] The hot pressing temperature was 90°C and the hot pressing time was 0.2 min.

[0155] The hot pressing pressure was 2 MPa.

[0156] The obtained composite solid electrolyte membrane is recorded as Li7-PEO-LiTFSI.

[0157] Related experiments and effect data:

[0158] The composite solid electrolyte membranes obtained in Example 1 and Comparative Example 1 were tested for AC impedance. The results are as follows: Figure 3 As shown, the results show that the impedance value of the composite solid electrolyte membrane in Example 1 is 22Ω, while the impedance value of the composite solid electrolyte membrane in Comparative Example 1 is 36Ω. Based on this, the impedance value in Example 1 is only 61% of the impedance value in the Comparative Example. The smaller the impedance value, the higher the ionic conductivity of the electrolyte.

[0159] The composite solid electrolyte membranes obtained in each embodiment and comparative example were cut using a film press to obtain disc-shaped membrane samples with a diameter of 16 mm. The disc-shaped membrane samples were then measured using a thin film thickness gauge to calculate the membrane thickness of each membrane sample. The results are shown in Table 1.

[0160] The impedance of the stainless steel blocking cell was tested by the EIS method for the composite solid electrolyte membrane, and the ionic conductivity of the composite solid electrolyte membrane at 20°C was calculated by the following formula:

[0161] σ=L / (R*S),

[0162] Where, σ is the ionic conductivity;

[0163] L is the thickness of the electrolyte membrane;

[0164] R is the body impedance;

[0165] S is the area of ​​the solid electrolyte membrane.

[0166] According to the above formula, the calculated ionic conductivity results are shown in Table 1.

[0167] Table 1. Membrane thickness and ionic conductivity of the composite solid electrolyte membranes of various embodiments and comparative examples.

[0168]

[0169]

[0170] As can be seen from Table 1, a preparation method of a composite solid electrolyte membrane provided in an embodiment of the present application uses polyethylene oxide and lithium carboxymethyl cellulose as raw materials to improve the ionic conductivity of the composite solid electrolyte membrane without adding an organic solvent; in addition, a plasticizer is added to the raw materials to improve the ionic conductivity of the composite solid electrolyte membrane. In addition, the use of the plasticizer can also improve the plasticity of the mixture, making it convenient to composite the solid electrolyte membrane only by hot pressing, thereby avoiding the use of a large amount of organic solvents; therefore, the preparation method can improve the ionic conductivity of the composite solid electrolyte membrane to 1.50×10 -4 S / cm or above while improving the environmental friendliness of the composite solid electrolyte membrane.

[0171] In addition, a method for preparing a composite solid electrolyte membrane provided in an embodiment of the present application uses a hot pressing dry processing technology and only uses a very small amount of plasticizer. The overall process is more environmentally friendly and safer than the traditional solution casting method.

[0172] In addition, a composite solid electrolyte membrane provided in an embodiment of the present application can improve the ionic conductivity of the composite solid electrolyte membrane to 1.50×10 -4 S / cm or more.

[0173] The above is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. It will be apparent to those skilled in the art that various modifications to these embodiments are possible, and the general principles defined in the present application can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to these embodiments shown in the present application, but will conform to the widest scope consistent with the principles and novel features applied for by the present application.

Claims

1. A method for preparing a composite solid electrolyte membrane, It is characterized in that The preparation method comprises: mixing polyethylene oxide, lithium carboxymethyl cellulose, and a lithium salt to obtain a mixture; Using a plasticizer to impregnate the mixture to promote a plasticization reaction of the mixture to obtain an impregnated mixture; vacuum drying the impregnated mixture to remove excess plasticizer to obtain a solid electrolyte membrane raw material; Hot pressing the solid electrolyte membrane raw material to obtain a composite solid electrolyte membrane; The weight m1 of the plasticizer and the weight m2 of the mixture satisfy the relationship: m1:m2=(0.9-1.1):

1.

2. The preparation method according to claim 1, It is characterized in that The soaking temperature is 75° C. to 85° C., and the soaking time is ≥12 h.

3. The preparation method according to claim 1, It is characterized in that The vacuum drying temperature is 75° C. to 85° C., and the vacuum drying time is 30 min to 120 min.

4. The preparation method according to claim 1, It is characterized in that The content of the residual plasticizer in the solid electrolyte membrane raw material and the mass ratio of the solid electrolyte membrane raw material satisfy: the residual plasticizer: the solid electrolyte membrane raw material ≤ 0.

1.

5. The preparation method according to claim 1, It is characterized in that The temperature of the hot pressing is 50° C. to 80° C., the time of the hot pressing is 0.5 min to 1.5 min, and the pressure of the hot pressing is 5 MPa to 20 MPa.

6. The preparation method according to claim 1, It is characterized in that The lithium salt comprises at least one of the following: Lithium bis(trifluoromethanesulfonyl imide), lithium perchlorate, lithium bis(fluorosulfonyl imide), lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium bis(oxalatoborate).

7. The preparation method according to claim 1, It is characterized in that The plasticizer comprises at least one of the following: Ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate.

8. The preparation method according to claim 1, It is characterized in that The weight m3 of the polyethylene oxide, the weight m4 of the lithium carboxymethyl cellulose and the weight m5 of the lithium salt satisfy the relationship: m3:m4:m5=(4-7):(4-1):

2.

9. A composite solid electrolyte membrane, It is characterized in that The composite solid electrolyte membrane is prepared by the preparation method according to any one of claims 1 to 8.

10. The composite solid electrolyte membrane according to claim 10, It is characterized in that The thickness of the composite solid electrolyte membrane is 20 μm to 200 μm.

Citation Information

Patent Citations

  • Preparation method of organic-inorganic composite solid electrolyte and electrolyte thereof

    CN112397770A

  • Sodium ion composite solid electrolyte and preparation method thereof

    CN113506910A

  • Preparation method of organic-inorganic composite solid electrolyte membrane

    CN116666735A

  • Method for preparing solid-state battery electrode and solid-state electrolyte membrane

    CN117895090A

  • Semi-solid state battery having high energy density and high safety and preparation method therefor

    WO2024138537A1